2016
DOI: 10.1002/bip.22990
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the interaction of proteins and disaccharides—The effect of pH and concentration

Abstract: To gain new insights into the interaction of proteins and disaccharides, we investigated the hydrodynamic radii, RhProt, of lysozyme molecules in solution and in a ternary protein-sugar-water system by PFG-NMR. Our approach is based on the assumption that the anhydrobiotic properties of disaccharides like trehalose are based on aggregation of sugar molecules to the proteins, i.e., accumulation of sugar molecules close to the protein, and that this process can be investigated by the experimentally detectable Rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…One such condition is the solution pH, which affects protein aggregation by causing changes in protein conformation and stability. [124][125][126] Filipe et al showed that immunoglobulin G1 (IgG1) transformed from dimers to micrometer-sized aggregates in a few hours when the pH decreased from 6 to pH 1. 127 The pH can cause differences in the growth of the nucleus and the rate of aggregation 128 by influencing protein-protein interactions, 129,130 the solubility of protein aggregates, 131 and the reactivity of protein cross-linking reactions.…”
Section: Ph and Ionic Strengthmentioning
confidence: 99%
“…One such condition is the solution pH, which affects protein aggregation by causing changes in protein conformation and stability. [124][125][126] Filipe et al showed that immunoglobulin G1 (IgG1) transformed from dimers to micrometer-sized aggregates in a few hours when the pH decreased from 6 to pH 1. 127 The pH can cause differences in the growth of the nucleus and the rate of aggregation 128 by influencing protein-protein interactions, 129,130 the solubility of protein aggregates, 131 and the reactivity of protein cross-linking reactions.…”
Section: Ph and Ionic Strengthmentioning
confidence: 99%
“…The analysis of solvent composition and HB patterns suggested that the sugar anchors a thin water layer at the protein surface, whose molecules bridge protein and matrix H-bond groups, reduce protein non-harmonic motions, and stabilize the protein conformation. Reducing the water content, a few direct protein-trehalose interactions start to emerge, indicating that the water replacement and water entrapment hypotheses are not mutually exclusive, but their occurrence depends only on external parameters, as hydration or sugar/protein ratio [163]. MD simulations showed also that trehalose could form patches around the protein, reducing the protein backbone flexibility [16,164].…”
Section: Effect Of Saccharide Matrices On Protein Structure and Dynamicsmentioning
confidence: 99%
“…This suggests that water replacement and water entrapment hypotheses are not mutually exclusive. Indeed, MD simulations show that trehalose could form patches around the protein, thereby reducing the flexibility of the protein backbone. , It has been observed that trehalose starts to form a protective coating at a high sugar/protein ratio …”
Section: Introductionmentioning
confidence: 99%
“…29,30 It has been observed that trehalose starts to form a protective coating at a high sugar/protein ratio. 31 The interactions between protein and matrix have been also studied on carboxy-myoglobin (MbCO) embedded in trehalose matrices at different residual hydrations, by Fourier transform infrared spectroscopy (FTIR). 32−34 In these studies, the CO stretching band (COB, ∼1900−2000 cm −1 ), one of the most studied protein spectroscopical markers, was used to account for the properties of the protein, 35,36 whereas the adjacent water association band (WAB, ∼2000−2400 cm −1 ) was employed for those of the matrix.…”
Section: ■ Introductionmentioning
confidence: 99%